2020
DOI: 10.1111/nph.16769
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the RNA polymerase subunit RpoB depends on RNA editing by OsPPR16 and affects chloroplast development during early leaf development in rice

Abstract: Plastid-encoded genes are coordinately transcribed by the nucleus-encoded RNA polymerase (NEP) and the plastid-encoded RNA polymerase (PEP). Resulting primary transcripts are frequently subject to RNA editing by cytidine-to-uridine conversions at specific sites. The physiological role of many editing events is largely unknown. Here, we have used the CRISPR/Cas9 technique in rice to knock out a member of the PLS-DYW subfamily of pentatricopeptide repeat (PPR) proteins. We found that OsPPR16 is responsible for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 108 publications
(130 reference statements)
0
24
0
Order By: Relevance
“…Previous studies have shown that plastid RNA editing plays an important role in regulating chloroplast development in plants (Xiao et al 2018 ; Huang et al 2020 ; Wang et al 2020 ). To verify whether the OsClpR1 mutation affects chloroplast RNA editing, we examined the RNA editing efficiency of 21 editing sites in wild-type and al3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that plastid RNA editing plays an important role in regulating chloroplast development in plants (Xiao et al 2018 ; Huang et al 2020 ; Wang et al 2020 ). To verify whether the OsClpR1 mutation affects chloroplast RNA editing, we examined the RNA editing efficiency of 21 editing sites in wild-type and al3 .…”
Section: Resultsmentioning
confidence: 99%
“…Specific cDNA fragments containing editing sites were amplified and sequenced. The cDNA sequences were compared to identify C to T changes resulting from RNA editing as previously described (Tan et al 2014 ; Cui et al 2019 ; Huang et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The E and DYW motifs are thought to be associated with RNA editing. QED1 and ECD1 in Arabidopsis ( Wagoner et al, 2015 ; Jiang et al, 2018 ) and PPR6 and PPR16 in rice ( Tang et al, 2017 ; Huang et al, 2020 ), which belong to the PLS-DYW subclass, all affect the RNA editing of different sites, and they can show varied levels of mutational phenotypes. Focusing here on PPR6, its corresponding ppr6 mutant showed early defective chloroplast development that led to albino leaves and eventual seedling death.…”
Section: The Function Of Ppr Proteins In the Chloroplastmentioning
confidence: 99%
“…PPR756, a member of the PLS-E subclass, participates in RNA editing events of atp6, ccmC, and nad7. The loss of PPR756 could cause abortive pollen development in rice (Zhang Q. et al, 2020). The P-subfamily PPR protein OsPPR939, which can be phosphorylated by OsS6K1, regulates plant growth and pollen development by splicing mitochondrial nad5 introns 1, 2, and 3 (Zheng et al, 2021).…”
Section: Ppr Proteins Manipulate Cytoplasmic Male Sterility-related Genesmentioning
confidence: 99%
“…Mutation of this gene will lead to impaired chloroplast development, a yellowing phenotype of seedlings and even death ( Hein and Knoop, 2018 ). OsPPR16, a PLS-DYW subfamily PPR protein, is responsible for RNA editing of the RNA polymerase subunit RpoB and affects Chl synthesis and efficient chloroplast development in rice ( Huang et al, 2020 ). The PPR protein DUA1 interacts with sigma factor 1 to form the PPR-SIG complex, and the module regulates chloroplast gene expression and chloroplast development in response to light and temperature ( Du et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%